Author Correction: Direct RNA Sequencing of the Coding Complete Influenza A Virus Genome. Issue 1 (December 2018) - Keller, Matthew; Rambo-Martin, Benjamin; Wilson, Malania; Ridenour, Callie; Shepard, Samuel; Stark, Thomas; Neuhaus, Elizabeth; Dugan, Vivien; Wentworth, David; Barnes, John
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.